ON THE RELATIONSHIP OF CHANGES IN CASPIAN SEA LEVEL TO NEOTECTONIC MOVEMENTS - Vdovykin G.P. (My University, 1990)
One of the leading causes of the variations in Caspian Sea level is neotectonic movements, whose pulsational character is determined by solar- (and lunar-) terrestrial relationships. Exogene factors also have their effect - the surface runoff of river waters, the cessation of evaporation of sea water in the Kara-Bogaz-Gol Gulf (since 1980), etc. On the basis of the cyclinal variations in the level of the Caspian Sea that have been discovered, this article proposes a method of graphic prediction of the maximal level of the Caspian Sea to the year 2100.